An overview of electronic waste threats and WEEE-RoHS regulations (Aintelia Science Notes, 2022)
world and another product is designed by adding to this product in another part. These designs, on the other hand, bring with them some threats and responsibilities. If each electrical/electronic device produced is not destroyed in appropriate environment and conditions after its useful life, or if it is not repaired and reused, it poses a danger to nature. When electrical and electronic devices, which are indispensable parts of our lives, become electronic waste (e-waste), harmful substances in their structures are unconsciously released into nature. As a result, environmental pollution increases. With the WEEE (Waste from Electrical and Electronic Equipment) and RoHS (Restriction of Hazardous Substances) regulations that the European Union came into force in 2003, it aimed to minimize the mixing of these harmful substances, which are hostile to the environment and human health, into nature, and to protect the environment and human health. In this study, a literature research was conducted on the consequences of electrical and electronic devices when they become e-waste, what harmful substances are in e-waste, the aims and scopes of WEEE and RoHS, which are European Union regulations. The result of a RoHS test that the manufacturer Emas has had for its products has been shown. With this study, it is aimed to raise awareness of consumers and producers about human-environmental health.
Keywords: Electronic Waste; Environmental Health; Human Health; WEEE; RoHS